Juridical Analysis Analisis Yuridis Pencemaran Laut Yang Disebabkan Limbah Plastik - Nining Yurista Prawitasari (JURNAL HUKUM PELITA, 2022)
Indonesia is referred to as a maritime country because the location of the archipelago becomes a sea traffic lane. Marine pollution is the entry or inclusion of living things, substances, energy, and/or other components into the marine environment by human activities so that they exceed the established quality standards of the marine environment. Marine pollution, especially that caused by plastic waste is a threat that really must be handled seriously. The purpose of the study was to determine the juridical basis and responsibility for marine waste pollution. The method of analysis is normative legal research, using a law approach, a case approach and a conceptual approach. The legal materials used in the research were collected by conducting searches and documentation studies, either through e-books, libraries and internet media. The results of the study show that the forms of legal liability for perpetrators who pollute the marine environment in Indonesia include administrative responsibility, civil liability, andcriminal liability. The application of imprisonment and fines is cumulative, not an alternative. So it is necessary both, namelyimprisonment and fines, not one of them. Currently, there is still a need for firm and real action from the government and publicawareness to tackle the problem of plastic waste in the sea.